Kinematics Modeling and Simulation of a Self-propelled Wrapping Packaging Robot - Chen Yu; Shi Yalei; Hu Yakai; Wang Liangwen; Liu Xuling; Jing Xiaodi (Jixie chuandong)
The development of the self-propelled wrap-around packaging robot can significantly boost the technological progress of the industry. This research introduces a self-propelled wrap-around packaging robot with a new working mode. For this packaging robot, the AGV equipped with a 6-DOFs robot arm to construct a mobile robot arm is used as the main body. The packaging film fixing device and the film drawing frame are loaded on the AGV, to realize the complete autonomous wrapping work. On the basis of introducing the overall structure of winding packaging robot, the working process of typical objects winding packaging with a mobile manipulator is analyzed and kinematics modeling is conducted. A simulation analysis system is developed based on the mathematical model of the mobile robot arm and the model of winding typical objects. The calculation and simulation results show that the wrap-around packaging robot can complete the wrapping work of packaging film and meet the design requirements. The related work provides a basis for the practical application of the self-propelled wrap-around packaging robot.